2017
DOI: 10.1080/21513732.2017.1360394
|View full text |Cite
|
Sign up to set email alerts
|

Tropical forest-transition landscapes: a portfolio for studying people, tree crops and agro-ecological change in context

Abstract: Nudging the development trajectory of tropical landscapes towards sustainability requires a global commitment and policies that take diverse contexts and forest transitions into account. Out-scaling and upscaling landscape-level actions to achieve sustainable development goals globally need to be based on understanding of extrapolation domains and interconnectivity of products and services. We evaluated three portfolios of tropical landscape observatories and quantified extrapolation domains across ecological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 59 publications
(66 reference statements)
0
39
0
Order By: Relevance
“…These differences may be caused by differences in forest types and the biodiversity metrics that were used [9]. However, the degree of causality and the relevance of such relationships beyond (modified) natural forests is still uncertain and its relevance in the face of global climate change is debated [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These differences may be caused by differences in forest types and the biodiversity metrics that were used [9]. However, the degree of causality and the relevance of such relationships beyond (modified) natural forests is still uncertain and its relevance in the face of global climate change is debated [18].…”
Section: Introductionmentioning
confidence: 99%
“…While becoming the largest cacao producing region of Indonesia, Sulawesi boomed in cacao-based land-use systems after 1980 [28], with further increased from 55,000 ha in 1990 to 230,000 ha in 2010, particularly in South and Southeast Sulawesi [29]. Due to its suitability to a broad range of climatic conditions, cacao may be as great a threat to tropical rainforests [18,30] as the more widely debated oil palm. Subsequent intensification in cacao agroforestry systems leads to shade tree removal, shifting the systems to become monoculture.…”
Section: Introductionmentioning
confidence: 99%
“…Based on a first comparison between cacao, coffee, rubber, oil palm and tropical timber, four formal propositions are formulated: 1) a strong and prominent issueattention cycle on ES threats and social problems drives sustainability concerns and actions; 2) dynamics within determinants of global value chain governance (positively and negatively) interact with the emergence of sustainability standards, initiatives and certification; 3) pressures from the public evoke sustainability initiatives and shift standards systems; 4) sustainability initiatives, standard settings and certification only provide partial solutions for ES and social problems. Dewi et al (2017) discusses pantropical data on the relations between people, forests and tree crops and uses these data to test the validity of the FTA tropical landscapes portfolio. The FTA portfolio provides a 5% sample of area, 8% of people, 9% of tree cover and 10-12% of potential tree crop presence across the tropics.…”
Section: Topics In the Special Issuementioning
confidence: 99%
“…As a sampling frame, we used a portfolio of Sentinel Landscapes (SLs) used across the three tropical continents. Dewi et al (2017) analysed the representativeness (and remaining biases) of this portfolio with respect to the issues of forest, human population density, deforestation rates and roles of the set of tropical tree crops studied here. The overall approach of the research project reported in this Special Issue is outlined below.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation